The Concept of 'Ana' According to Badiuzaman Said Nursi and Contemporary Psychological Discussion - Arroisi, Jarman; Yuwanda, Netty (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2020)
This article examines the concept of